2020
DOI: 10.3389/fmicb.2020.01973
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and Macrophage-Mediated Pathology and Protective Immunity During Schistosomiasis

Abstract: Infection by Schistosoma parasites culminates in a chronic granulomatous disease characterized by intense tissue fibrosis. Along the course of schistosomiasis, diverse leukocytes are recruited for inflammatory foci. Innate immune cell accumulation in Th2-driven granulomas around Schistosoma eggs is associated with increased collagen deposition, while monocytes and macrophages exert critical roles during this process. Monocytes are recruited to damaged tissues from blood, produce TGF-β and differentiate into mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 97 publications
0
20
0
6
Order By: Relevance
“…We found that LCN2 may be a positive regulator of macrophage M1 polarization and is closely related to cytokines. Macrophage M1 polarization may reduce liver fibrosis induced by S. japonicum ( Souza et al., 2020 ). Our data revealed that the elevated LCN2 expression in S. japonicum infection might be a positive factor against it by upregulating INOS-mediated activation of macrophage M1.…”
Section: Discussionmentioning
confidence: 99%
“…We found that LCN2 may be a positive regulator of macrophage M1 polarization and is closely related to cytokines. Macrophage M1 polarization may reduce liver fibrosis induced by S. japonicum ( Souza et al., 2020 ). Our data revealed that the elevated LCN2 expression in S. japonicum infection might be a positive factor against it by upregulating INOS-mediated activation of macrophage M1.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral monocytes, which are recruited to the site of infection, produce TGF-β and differentiate into monocyte-derived CX 3 CR1 + macrophages, which become alternatively activated due to IL-4/IL-13 signaling via IL-4Rα. This type of macrophage is further characterized by transcription of Arg1, Chi3l3, Relma, and Mrc1 , which is coordinated by STAT6 [ 98 ]. Furthermore, these macrophages are potent producers of pro-fibrinogenic cytokines such as IL-10 and TGF-ß.…”
Section: Infectious Microbial Challenges Affecting the Livermentioning
confidence: 99%
“…Furthermore, these macrophages are potent producers of pro-fibrinogenic cytokines such as IL-10 and TGF-ß. Interestingly, it seems that recruited Ly6C hi monocytes during schistosomiasis transition directly into alternatively activated macrophages without first adopting the phenotype of Ly6C lo monocytes [ 98 ]. However, Ly6C lo and intermediate Ly6C cells also contribute to pathogenicity; indeed, reduced hepatic accumulation observed in mice with reduced expression of CD18 (ß 2 integrin receptor subunit) results in increased formation of granulomatous lesions in the liver, increased egg deposition, and increased mortality [ 99 ].…”
Section: Infectious Microbial Challenges Affecting the Livermentioning
confidence: 99%
“…TLRs are expressed by immune cells, like macrophages, dendritic cells (DCs), and neutrophils [ 16 ]. Macrophages resist parasitic infection through phagocytosis, antigen presentation, and activation of other immune cells [ 17 ]. TLRs play a double-edged sword role in parasitic infections.…”
Section: Introductionmentioning
confidence: 99%